The Hall effect on MHD 2-fluid unsteady heat transfer flow of plasma in a rotating system via a straight channel between conducting plates - Linga Raju, Temburu; Venkata Rao, B. (Zielona Góra: Uniwersytet Zielonogórski)
Hall currents are used to investigate MHD unsteady two fluid flows and heat transport of plasma along a straight channel of conducting plates. In the two liquid zones, the velocity and temperature fields for the case of conducting side plates are obtained by solving the governing equations using a two-term series under the specified conditions.
Keywords: unsteady flow; MHD; immiscible flow; heat transfer; Hall effect; plasma; rotating frame; conducting plates